Perhitungan Harga Pokok Produksi dengan Metode Full Costing dan Variabel Costing untuk Menentukan Harga Jual - Deshinta Arrova; Etti Ernita Sembiring (Indonesian Accounting Literacy Journal, 2023)
The calculation of the cost of production is an important thing to note because competition between UMKM in producing quality products is increasing the company has not calculated all the elements of factory overhead costs. This study aims to find out how to calculate the cost of production using the Full Costing method to determine the selling price of products at UMKM Gunung Djaya. The full costing method is a method of determining product cost that considers all elements of production costs consisting of raw materials, direct labor costs and factory overhead costs, both fixed and variable. The research method used in this research is data analysis method with descriptive analysis. The data source used is primary data. Primary data obtained from interviews conducted with company owners. Data collection techniques were carried out by interviewing documentation and observation. This study uses 7,000 sample orders during January 2023. The selling price can be obtained from the cost of production plus the expected profit. The results of the study stated that the calculation of the cost of production using the full costing method resulted in a difference that affected the selling price.